Toward more nutritious diets for young children in southern Bangladesh: Assessing the contribution of Community Nutrition Scholars and identifying constraints to utilization of orange-fleshed sweetpotato - Prain, Gordon (International Potato Center, 2020)
This study seeks to assess progress so far towards achieving Output 4 of the project ‘Strengthening food system resilience in Asia's mega deltas with salt-tolerant sweetpotato and potato’, namely increased utilization of improved OFSP and P varieties by target households (HHs), especially to support and improve the nutrition of small children. The intervention strategy to achieve that output involved combining nutrition and hygiene education given by a cadre of community nutrition scholars (CNS) to mothers of small children combined with the distribution of planting material of nutritionally beneficial crops to those women. This assessment uses sexspecific Focus Group Discussions (FGDs) with selected women participants in the training and selected male spouses or other male relatives of women who participated, with one female and one male FGD located in each of the sub-districts (upazilas) targeted in the training interventions. In addition, two FGDs were conducted with CNS, one in each of the target districts. FGDs were adapted to the conditions of the coronavirus pandemic, so numbers of women and men were smaller than a normal FGD and the timing of the FGD shorter. The CNS FGDs were maintained at a more regular size (10 persons) to capture experiences from the different sub-districts. The FGDs aimed to understand whether the participation by mothers in the CNS training program resulted in changes in mothers’ and fathers’ knowledge and behavior that in turn contributed to children’s improved nutrition and health. The study also examined what were the specific constraints and opportunities involved in the utilization of OFSP as a nutritional food for young children.